Mining key genes for ramie (Boehmeria nivea L.) adaptation to poor soil condition using transcriptome analysis - Wu, Shenglan; Jie, Hongdong; Xing, Hucheng; Jie, Yucheng (Frontiers in Sustainable Food Systems, 2025)
IntroductionAgricultural land degradation threatens food security and agricultural ecosystem sustainability, necessitating phytoremediation to address this problem. Ramie (Boehmeria nivea L.), a cash crop known for its resilience in marginal environments and multiple ecological benefits, represents a promising candidate for this purpose. However, lack of varieties tolerant to poor soil limits this potential, necessitating genetic improvement.MethodsThis study was therefore designed to identify key genes involved in ramie’s adaptation to poor soil conditions and to further explore the underlying molecular mechanisms. Leaf RNA from two ramie varieties, the tolerant Xiangzhu XB (XZ-XB) and the sensitive Xiangzhu 3 (XZ-3), was analyzed using high-throughput sequencing.ResultsAfter processing high-quality clean data, comparative transcriptome analysis revealed 1,908 differentially expressed genes (DEGs) between XZ-XB and XZ-3, among which 1,116 were up-regulated and 792 were down-regulated in XZ-XB relative to XZ-3. Notably, four up-regulated DEGs displayed fold changes greater than 9,500, while four down-regulated DEGs showed fold changes exceeding 1,000. Functional annotation linked the DEGs to critical processes as transporter activity, proteases regulation, purple acid phosphatase activity, etc. The findings also revealed that tolerant genotype likely enhance survival under poor soil condition by down-regulating senescence-promoting genes and up-regulating stress-signaling pathways.DiscussionResults of this study provide valuable genetic resources and candidate targets for molecular breeding of ramie varieties with enhanced resilience to nutrient-poor soils. By the help of molecular breeding, the process will be speed up to develop nutrients-deficiency resilient ramie varieties as a sustainable, plant-based strategy for restoring degraded agricultural ecosystems and enhancing land productivity.